Sequential Monitoring for Changes in Models with a Polynomial Trend. Issue 1 (2nd January 2016) - Qi, Peiyan; Duan, Xifa; Tian, Zheng; Li, Fuxiao
Abstract : This article considers, for the first time, sequential monitoring procedures that detect possible parameter changes in the polynomial trend models. A new class of sequential monitoring procedures that based on generalized fluctuation testing principle is proposed. The asymptotic null distributions and the consistency of the proposed tests are derived and their asymptotic critical values are tabulated. The methods are illustrated and compared in a small simulation study. In particular, we apply the proposed tests to investigate the Chinese commodity retail sales and consumer price indexes. Simulations and applications support our method.